Introduction to pharmacoepidemiology - Wong, Angel (Henry Stewart Talks, 2025)
Pharmacoepidemiology, Epidemiology, Thalidomide, Autism spectrum disorder (ASD), Randomised controlled trial (RCT), Clarithromycin, Alendronate